Classification of Fibrillation Organisation Using Electrocardiograms to Guide Mechanism-Directed Treatments - Li, Xinyang; Shi, Xili; Handa, Balvinder S.; Sau, Arunashis; Zhang, Bowen; Qureshi, Norman A.; Whinnett, Zachary I.; Linton, Nick W. F.; Lim, Phang Boon; Kanagaratnam, Prapa; Peters, Nicholas S.; Ng, Fu Siong (Frontiers in Physiology, 2021)
Atrial fibrillation (AF) and ventricular fibrillation (VF) are complex heart rhythm disorders and may be sustained by distinct electrophysiological mechanisms. Disorganised self-perpetuating multiple-wavelets and organised rotational drivers (RDs) localising to specific areas are both possible mechanisms by which fibrillation is sustained. Determining the underlying mechanisms of fibrillation may be helpful in tailoring treatment strategies. We investigated whether global fibrillation organisation, a surrogate for fibrillation mechanism, can be determined from electrocardiograms (ECGs) using band-power feature analysis and machine learning. In this study, we proposed a novel ECG classification framework to differentiate fibrillation organisation levels. Band-power features were derived from surface ECGs and fed to a linear discriminant analysis classifier to predict fibrillation organisation level. Two datasets, single-channel ECGs of rat VF (n=9) and 12-lead ECGs of human AF (n=17), were used for model evaluation in a leave-one-out manner. The proposed method correctly predicted the organisation level from rat VF ECG with sensitivity of 75%, specificity of 80%, and accuracy of 78%, and from clinical AF ECG with sensitivity of 80%, specificity of 92%, and accuracy of 88%. Our proposed method can distinguish between AF/VF of different global organisation levels non-invasively from the ECG alone. This may aid in patient selection and guiding mechanism-directed tailored treatment strategies.